A Second Chance? The Labor Market Outcomes of Reforming Access to Adult Education - Patrick Bennett; Richard Blundell; Kjell G. Salvanes (Center for Economic Studies and ifo Institute (CESifo), 2021)
Developing effective tools to address prime-aged high school dropouts is a key policy question. We leverage high quality Norwegian register data to examine the labour market outcomes of expanding access to adult workers and exploit a large policy reform which greatly enabled access to high school education for adults. Our focus is on women and the results show a large and significant increase in education investments with a strong rise in the rate of college completion, leading to higher earnings, increased employment, and decreased fertility. They also point to an effective policy to reduce the gender earnings gap.
Keywords: I26; I28; J13; 330; adult education; returns to education; fertility; gender inequality